Correlates of HIV infection among female sex workers in Vietnam: Injection drug use remains a key risk factor. (1st May 2015) - Le, Linh-Vi N.; Nguyen, Tuan A.; Tran, Hoang V.; Gupta, Nisha; Duong, Thanh C.; Tran, Ha T.T.; Nadol, Patrick; Sabin, Keith; Maher, Lisa; Kaldor, John M.
Highlights: Injection drug use was key risk factor for HIV among female sex workers in Vietnam. Heroin injection, not methamphetamine use, continued to be main drug risk behavior. In cities with high HIV prevalence, non-injection drug use and inconsistent condom use were associated with HIV. Where HIV prevalence was low, selling sex on the street was associated with HIV. Abstract: Objective: Women who sell sex and use drugs have dual risks for HIV infection. Despite increasing reports of drug use among female sex workers (FSW) in Vietnam, FSW HIV interventions remain focused mainly on sexual risk reduction. We assessed the impact of drug use and inconsistent condom use on HIV infection among FSW in Vietnam, which few studies have quantified. Methods: We surveyed 5298 women aged ≥18 years who had sold sex in the past month from ten geographically dispersed provinces. We performed multivariate logistic regression on data from provinces with high (≥10%) or low (<10%) HIV prevalence among FSW. Results: Compared to FSW who never used illicit drugs, the odds of HIV infection among FSW who had ever injected drugs and those who reported non-injection drug use were 3.44 (CI 2.32–5.09) and 1.76 (CI 1.14–2.71), respectively, in high-prevalence provinces. FSW who always used condoms with clients had lower odds of HIV infection than those who did not (AOR = 0.71; CI 0.52–0.98). In low-prevalence provinces lifetime injection drug use (AOR 22.05, CI 12.00–40.49), but not non-injecting drug use or inconsistent condom use, was significantly associated with HIV infection. Conclusions: Because injection drug use and inconsistent condom use were key risk factors for HIV infection in high-prevalence provinces, drug injection risk reduction should be as much a focus of HIV prevention as sexual risk reduction. Where HIV prevalence remains low in FSW, a more general emphasis on harm reduction for all drug users will benefit FSW.